THE USE OF DIFFERENT STAINING METHODS TO EVALUATE THE DEVELOPMENT AND VIABILITY OF BOVINE EMBRYOS OBTAINED IN VIVO AND IN VITRO - Sri Gustari; Julian A.Bartolome Julian A.Bartolome Julian A.Bartolome (Jurnal Sain Veteriner, 1995)
In an attempt to find a good method to evaluate embryos we classified the in vitro embryos into freezable and non-freezable by subjective method. These embryos were compared with in vivo freezable embryos using Giemsa staining. The embryo development and viability was evaluated by fluorescent stain (PDA and Hoechst 33342) and compared with the result after Giemsa stain.That number of cells in freezable in vitro and in vivo embryos were not different (P > 0.1), while in vitro fresszable and non-freezable embryos showed significantly differences (P < 0,001) in number of cells.The agreement between Hoechst 33342 and Giemsa stain was quite high (63%) in embryos with number of cells less than 20, and low agreement (25 - 34 %) in embryios with number of cells more than 20. There was a significantly correlation (0.82) betwen the degree of fluorescent of FDA stain and the number of cells at Giemsa stain.The subjective classification of in vitro embryos can be used in the practical situation. PDA staining is a good tool to check this classification as well as to evaluate the development and viability of embroys in different step of experimental trials. Hoechst can be a valuable